Triple Helix Governance for Strengthening Islamic Boarding School Agribusiness - Afrilia, Merina; Sulistiawati, Henny; Astuti, Widya; Pratama, M Aviv Adhitya Putra (Kemudi, 2026)
Islamic boarding schools increasingly function not only as religious educational institutions but also as drivers of local economic development. This study aims to analyze the implementation of Triple Helix Governance in strengthening Islamic boarding school–based agribusiness through the Trubus Sentra Agrobisnis (TSA) Producer Cooperative in Paser Regency. This research applies a qualitative case study method using interviews, observation, and document analysis to explore collaboration among government institutions, business actors, and research organizations. The results show that the development of TSA is supported by strong collaboration among key stakeholders. Government institutions provide policy support and facilitation, research institutions contribute technological innovation, while business actors and zakat-based organizations strengthen economic networks and production capacity. This collaborative governance model enhances institutional capacity and supports sustainable agribusiness development. The study demonstrates that Islamic boarding schools can transform into community-based economic institutions through cooperative mechanisms. The integration of religious values, innovation, and policy support makes TSA a replicable model for strengthening local agribusiness governance and sustainable regional development.